2014
DOI: 10.1136/bcr-2014-204995
|View full text |Cite
|
Sign up to set email alerts
|

Multiple territory watershed infarcts following spinal anaesthesia

Abstract: Hypotension is one of the most common complications of spinal anaesthesia (SA). The intraoperative drop in the blood pressure is clearly associated with increased morbidity and mortality. In order to increase the awareness of this complication, we report a case of devastating stroke following an SA in a previously well woman with risk factors for vascular diseases. The patient developed multiple territory watershed infarcts and she eventually died from aspiration pneumonia 14 days after hospitalisation. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…10,42,68 Hypoxia also caused a sustained increase in expression of Rabep2, a novel gene that is critical in the VEGFA!Flk1!Rabep2!Notch!ADAM10/ 17!Clic4 pathway that directs collaterogenesis during development. 10,12,69 Our observation that hypoxic NCF was blocked in Rabep2 À/À mice is consistent with evidence that reduced oxygen, which under baseline conditions in normoxia is lowest in the vessels within the watershed zone between adjacent arterial trees, [70][71][72][73][74][75] induces the same or a similar pathway in the adult.…”
Section: Durability Of Hypoxic Neo-collateral Formation Collateral Rsupporting
confidence: 88%
See 1 more Smart Citation
“…10,42,68 Hypoxia also caused a sustained increase in expression of Rabep2, a novel gene that is critical in the VEGFA!Flk1!Rabep2!Notch!ADAM10/ 17!Clic4 pathway that directs collaterogenesis during development. 10,12,69 Our observation that hypoxic NCF was blocked in Rabep2 À/À mice is consistent with evidence that reduced oxygen, which under baseline conditions in normoxia is lowest in the vessels within the watershed zone between adjacent arterial trees, [70][71][72][73][74][75] induces the same or a similar pathway in the adult.…”
Section: Durability Of Hypoxic Neo-collateral Formation Collateral Rsupporting
confidence: 88%
“… 11 , 12 Perfusion of the plexus by the adjacent arterial trees normally proceeds down the trees’ pressure gradients and venous outflow pathways. 87 89 At baseline, oxygen content within watershed capillaries is low because they are the “furthest away from the aorta,” which is consistent with the watershed stroke phenomenon 70 75 ; the above-mentioned negligible flow in collaterals at baseline would also favor their PO 2 values being closer to tissue PO 2 . In the case of systemic hypoxemia, the PO 2 in watershed capillaries declines further and activates the collaterogenesis signaling pathway.…”
Section: Discussionsupporting
confidence: 55%
“…It is generally considered that postoperative stroke is multifactorial, and intraoperative hypotension may aggravate the pathological process by increasing the infarction size 26,27 . Furthermore, a decrease of MAP by more than 30% from baseline is significantly associated with the occurrence of a postoperative stroke 34 , and watershed infarct is associated with hypotension following spinal anesthesia 35 . By postoperative MRI examination, we confirmed that watershed infarct is absent in the three patients.…”
Section: Discussionmentioning
confidence: 99%